Dampak Merger & Akuisisi Pada Kinerja Keuangan: Studi Pada Perusahaan Non Keuangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016 - Stevanie ,Bonnie Mindosa (Jurnal Manajemen, 2019)
Merger and acquisition are one of many growth strategies that can be opted by a firm in order to gain competitive advantages. Merger is business combination from two different companies become one entity that still alive and the others is liquidate meanwhile acquisition is a take over of one company. This research aims to examine the effect of merger and acquisition activities on the company's financial performance which can be measured by using financial ratios, such as current ratio, net profit margin, return on assets, and debt to equity. This research provides evidence about the comparison of financial performance before and after mergers and acquisitions. This research using purposive sampling method and sample of this research consist of 35 companies listed on the Indonesia Stock Exchange in since 2012 to 2016. This research is using paired sample t-test and Wilcoxon test. The result from this research showed current ratio (CR), return on asset (ROA) and debt to equity (DER) did not show significantly difference after merger and acquisitions. But the net profit margin (NPM) showed difference after merger and acquisitions significantly. The conclusion from this research, there are not significantly differences for financial performance before and after merger and acquisition.Keywords: Mergers and Acquisitions, Financial Ratio, Paired Sample t Test, Wilcoxon Signed Rank Test